Hukum Perkawinan Berbeda Agama Menurut Kompilasi Hukum Islam (KHI) - Muhammad Shaleh (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The marriage law of different religions according to KHI. The purpose of this research is the response to a phenomenon that often occurs recently in society, especially urban communities. Interfaith marriages are taboo, because marriage is something sacred. Because every religion, especially Islam, has very clearly regulated marriage procedures. If there is a marriage of different religions, it is feared that there will be deviations in religion, because in fact marriage is to perfect religion and marriage is a very noble worship. Interfaith marriages will obscure the position of the wife, the lineage of a child's descendants, and of course the applied religion will be mixed with the teachings of the partner's religion and Islam itself prohibits interfaith marriages on these grounds. Interfaith marriages will only cause problems, so many parties are against this interfaith marriage, because by looking at facts like this, we can argue that interfaith marriages have been a debate for a long time. And although the formal legal acknowledgment of this permit has not been written, in practice the number of people who marry between different religions continues to increase, so how exactly does the legal view of the compilation of Islamic law respond to this problem. In this study, it will be explained globally about the marriage law of different religions and the reality that occurs in society. Keywords: Marriage Law, Different Religions, KHI